1995
DOI: 10.1074/jbc.270.38.22548
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of CYP1A1 by Indolo[3,2-b]carbazole in Murine Hepatoma Cells

Abstract: To determine the basis for unexpected differences in CYP1A1 inducing potencies and efficacies for the dietderived indole derivative, indolo[3,2-b]carbazole (ICZ) and 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD), we conducted a systematic analysis of events involved in the induced expression of CYP1A1 in murine hepatoma-derived cell lines (Hepa-1). In contrast to the effects of TCDD, induction kinetics and CYP1A1 mRNA half-life were dependent on ICZ concentration, and the response from low doses of inducer was tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(49 citation statements)
references
References 44 publications
1
48
0
Order By: Relevance
“…Moreover, these earlier studies did not reveal that dioxin up-regulated EPO mRNA. This may be due to the use of a weaker agonist than dioxin, or to the fact that readily metabolized agonists do not exhibit their activity for the prolonged time periods as compared with dioxin (33,34). Thus the differences in EPO response may simply be due to the different time points examined in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, these earlier studies did not reveal that dioxin up-regulated EPO mRNA. This may be due to the use of a weaker agonist than dioxin, or to the fact that readily metabolized agonists do not exhibit their activity for the prolonged time periods as compared with dioxin (33,34). Thus the differences in EPO response may simply be due to the different time points examined in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, in contrast to dioxin, ICZ is metabolically labile, and for this reason, the effects of ICZ are very different from those of dioxin (54). More specifically, experiments with animals have shown that the administration of one dose or repeated doses cannot affect significantly the food intake of experimental animals, in contrast to dioxin.…”
Section: Malassezia-produced Ahr Ligands and Significance Of Ahr Actimentioning
confidence: 99%
“…Other acid catalyzed products of I3C likely account for the ability of dietary I3C to markedly reduce the incidence of estrogenresponsive mammary tumors in rodents. Several studies have shown that ICZ binds to the aromatic hydrocarbon (Ah) receptor and induces P450 CYP1A1 gene expression, which can alter estrogen metabolism [18,24,25]. However, at least one of the acid catalyzed products, CTr, is a strong estrogen receptor agonist capable of increasing the proliferation rate of cultured human breast cancer cells [22].…”
Section: Introductionmentioning
confidence: 99%